Kegiatan Eksplorasi untuk Meningkatkan Kreativitas Anak Usia Dini di TK Islam Baiturrahim Jambi - Wanti Hasmar; Indah Permata Sari; Mawaddah Warahmah (Jurnal Abdimas Kesehatan (JAK), 2021)
Exploration is looking for or doing exploration with the aim of finding something. Considering that early childhood does not need theory intake, the learning process is designed using practical activities in the surrounding environment through exploration activities. The teacher's job is only as a companion and facilitator. Community service activities will be carried out in May-June 2021 with the method of discussion and delivering materials and leaflets related to the education of kindergarten children's exploration activities. The leaflet consists of 3 activities, namely water play activities, sand play and gardening activities. This Community Service (PKM) aims to be used as a source of knowledge for parents of children in Baiturrahim Islamic Kindergarten Jambi. The results of the evaluation through the question and answer are that on average the parents of kindergarten children understand and can implement exploration activities in order to increase the creativity of kindergarten children